Current Progress in Hydrometeorological Observations and Modeling - Mason, Alfredo (USA States Academic Press, 2023)
The branch of study that focuses on the energy, chemistry, physics, and water fluxes in the atmosphere and Earth$1 (Bs surface is known as hydrometeorology. Hydrometeorological hazards originate due to extreme meteorological and climatic occurrences having atmospheric, hydrological, or oceanographic origin. A few examples of hydrometeorological hazards include typhoons, hurricanes, floods, drought, heatwaves, cold spells, and coastal storm surges. Hydrometeorological monitoring systems are required to develop adequate preparedness and mitigation strategies. The hydrometeorological phenomena can be modeled in three major ways, namely, nowcasting, numerical weather prediction, and statistical techniques. Nowcasting refers to the weather forecasting on a very short mesoscale period. This book traces the progress of hydrometeorology, and highlights some of its key concepts and applications. It unfolds the innovative aspects of hydrometeorological observations and modeling, which will be crucial for the progress of this field in the future. The book is appropriate for students as well as for experts seeking detailed information in the area of hydrometeorology.s
Keywords: Hydrometeorology; Meteorology; Atmospheric Science